First description of natural concomitant infection of avian nephritis virus and infectious bronchitis virus reveals exacerbated inflammatory response and renal damage in broiler chicks. (May 2021) - Munuswamy, Palanivelu; Ramakrishnan, Saravanan; Latheef, Shyma K.; Kappala, Deepthi; Mariappan, Asok Kumar; Kaore, Megha; Anbazhagan, Karthikeyan; Puvvala, Bhavani; Singh, Karam Pal; Dhama, Kuldeep
Abstract: We describe the first report on spontaneous Avian Nephritis Virus (ANV) and Infectious Bronchitis Virus (IBV) concurrent infection in broiler chicks. On necropsy, the kidneys were found swollen with its parenchyma and ureters stuffed with urate flakes. Histopathologically, the renal tubular damage and inflammatory response were severe in concurrently infected birds compared to the cases infected only with ANV, which had direct correlation with significantly (p < 0.001) increased expression of IL-1 β, IL-4, IL-12, IL-13, iNOS and IFN-γ transcripts in the kidneys of concurrently infected birds. Relative decrease in IFN-β transcript levels in the concurrently infected birds indicates suppression of antiviral response; the iNOS level was manifold increased which can be attributed to the enhanced macrophage response. Nucleotide sequencing of S1-spike glycoprotein gene of IBV and RNA dependent RNA polymerase gene of ANV confirmed etiologies as Igacovirus of Gammacoronavirus and ANV-2 of Avastrovirus 2, respectively. Both ANV and IBV virus affect kidneys. Our findings suggested that concurrent infections of these two viruses might have enhanced the transcripts of Th1, Th2 and proinflammatory cytokines with reduced IFN-β transcripts resulting in decreased host innate antiviral mechanisms leading to exacerbated renal lesions. Future experimental co-infection studies could throw more lights on pathology and pathogenesis during concurrent infections of ANV and IBV in poultry. Highlights: First repot of avian nephritis virus (ANV) and infectious bronchitis virus (IBV) concurrent infection is described The ANV and IBV concurrent infection exacerbated renal lesions in commercial chicken flocks. The differential expression of cytokine transcripts might have contributed to the inflammatory response and renal lesion.